2017
DOI: 10.18632/oncotarget.15609
|View full text |Cite
|
Sign up to set email alerts
|

Tumor and serum gamma-glutamyl transpeptidase, new prognostic and molecular interpretation of an old biomarker in gastric cancer

Abstract: BackgroundGastric Cancer is one of the most lethal malignancies worldwide. Gamma-glutamyl transpeptidase (GGT) is an enzyme mainly involved in cellular glutathione homeostasis. We aim to explore the clinical value of GGT in gastric cancer.ResultsAmong 322 patients enrolled, 65/82 patients were determined as GGT positive in serum/tumor, respectively. High tumor GGT expression is significantly associated with lymph node metastasis, histological subtype, and Her2 expression. Kaplan-Meier curve shows that high tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 46 publications
3
42
0
1
Order By: Relevance
“…In this study, the investigators hypothesized that GGT might be associated with tumor development. Wang et al [ 20 ] found that the expression of GGT in tumor cells was increased, which could promote the development and invasion of gastric cancer. Moreover, previous studies have confirmed that GGT can affect the sensitivity of tumor cells to drugs [ 17 21 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the investigators hypothesized that GGT might be associated with tumor development. Wang et al [ 20 ] found that the expression of GGT in tumor cells was increased, which could promote the development and invasion of gastric cancer. Moreover, previous studies have confirmed that GGT can affect the sensitivity of tumor cells to drugs [ 17 21 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, GGT may directly participate in the progression of cancer, as studies on melanoma cells found that elevated GGT activity resulted in a growth advantage both in vitro and in vivo [27]. Moreover, a newly published study using geneset enrichment analysis (GSEA) reported that in gastric cancer patients, GGT was significantly associated with EMT, KRAS, SRC and PKCA signaling pathways [13], which are involved in cancer progression and metastasis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are also pathways implicated in cancer development and progression, and positive GGT associations with risks of various cancer types have been demonstrated by several prospective studies [9][10][11][12]. Quite opposite to the abundance of cancer risk studies, relatively few studies have investigated the prognostic role of serum GGT in cancer outcomes: increased serum GGT has been inversely associated with survival in gastric cancer [13], colorectal cancer [14], ovarian cancer [15], breast cancer [16], endometrial cancer [17,18], cervical cancer [19], and renal cell carcinoma [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, GGT may directly participate in progression of cancer, as studies on melanoma cells found that elevated GGT activity resulted in growth advantage both in vitro and in vivo [27]. Moreover, a newly published study using gene set enrichment analysis (GSEA) reported that in gastric cancer patients, GGT was significantly associated with EMT, KRAS, SRC and PKCA signaling pathways [13], which are involved in cancer progression and metastasis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are also pathways implicated in cancer development and progression, and positive GGT associations with various cancer types have been demonstrated by several prospective studies [9][10][11][12]. Quite opposite to the abundance of cancer risk studies, only a few studies have investigated a prognostic role of serum GGT in cancer outcomes: increased serum GGT has been inversely associated with survival in gastric cancer [13], colorectal cancer [14], ovarian cancer [15], breast cancer [16], endometrial cancer [17,18], cervical cancer [19], and renal cell carcinoma [20].…”
Section: Introductionmentioning
confidence: 99%